Uji Coba Media Diari Giziku Pada Siswa di SDS IT AL Wahdah Kota Kendari Tahun 2024 - Devi Savitri Effendy; Nabila Dwi Saputri; Hartati Bahar; Hariati Lestari; Febriana Muchtar; Ramadhan Tosepu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Multiple nutrition remains a major problem in Indonesia, including among school-age children, which can affect the quality of human resources in the future. School-age children are a group that is vulnerable to nutritional problems because they need diverse food intake for optimal growth and development. The purpose of this activity is to determine the difference in students' knowledge about balanced nutrition before and after being given education through my nutrition diary media at SDS IT ALWahdah Kendari in 2024. Data were collected through questionnaires distributed both before and after education, using the Diari Giziku book media. Students who will receive education are 35 students. The assessment results of the paired sample t-test test show the p-value of knowledge (0.000) < α (0.05), attitude (0.000) < α (0.05), and motivation (0.000) < α (0.05), meaning that there is a difference in knowledge before and after being given education through my nutrition diary media, therefore it can be concluded that my nutrition diary media is a medium that can increase students' understanding of balanced nutrition.